TRANSITION OWNERSHIP RIGHTS LAND OF AGRICULTURAL LAND WITH ABSENTE USING E-KTP IN BANGLI DISTRICT - S. Sarbini; I Ketut Adhi Karunia Jaya Negara (Warmadewa Press, 2023)
One of the objectives of land reform is to hold a fair and equitable distribution of the livelihoods of the peasants in the form of land so that with this distribution a fair and equitable distribution of results can be achieved. The purpose of this land reform is realized through the determination of the minimum area and maximum area of agricultural land ownership with certain rights by one family or legal entity. Prohibition of agricultural land ownership in absentee is a prohibition on ownership of agricultural land located outside the area where the owner lives. One of the efforts to prevent absentee land ownership is the existence of an Electronic Identity Card. However, the implementation of the transfer of rights based on the sale and purchase of agricultural land, with the implementation of the E-KTP, was not carried out perfectly. This research aims to examine the implementation of the absentee sale and purchase of agricultural land rights using E-KTP in Bangli Regency. The research method used is empirical legal research and the research locations were held in Bangli Regency, PPAT and the Bangli Regency Land Office. The results of this research showed that the implementation of an E-KTP nationally, still cannot overcome the ownership of agricultural land in Bangli Regency by people who have addresses outside the Bangli Regency sub-district and still carry out the process of changing addresses so as not to cause absentees.